Inequality and Welfare Dynamics in the Russian Federation during 1994-2015 - Hai-Anh H. Dang; Michael M. Lokshin; Kseniya Abanokova; Maurizio Bussolo (Global Labor Organization (GLO), 2019)
Russia offers the unique example of a leading centrally planned economy swiftly transforming itself into a market-oriented economy. We offer a comprehensive study of inequality and mobility patterns for Russia, using multiple rounds of the Russian Longitudinal Monitoring Surveys over the past two decades spanning this transition. We find rising income levels and decreasing inequality, with the latter being mostly caused by pro-poor growth rather than redistribution. The poorest tercile experienced a growth rate that was more than 10 times that of the richest tercile, leading to less long-term inequality than short-term inequality. We also find that switching from a part-time job to a full-time job, from a lower-skill job to a higher-skill job, or staying in the formal sector is statistically significantly associated with reduced downward mobility and increased income growth. However, a similar transition from the private sector to the public sector is negatively associated with income growth.
Keywords: C15; D31; I31; O10; O57; 330; welfare dynamics; poverty; inequality; pro-poor growth; panel data; household surveys; Russia